Accessibility Design Issues with Malaysian News Websites: a Case Study Using a Checker and WAVE - Azwa Yazid, Mariam; Hazri Jantan, Azrul; Azim Abd Ghani, Abdul; Kamaruddin, Azrina; Admodisastro, Novia (International Journal of Engineering and Technology, 2018)
The objective of this research is to provide public society and web developers with a higher level of awareness on web accessibility issues in Malaysian websites. The finding is extremely crucial to avoid discrimination among the disable community to use Information and Communication Technologies (ICT) in their daily lives. Accessibility evaluation has been performed on four Malaysian broadsheet news websites using two online automated tools. The analysis is based on the compliance level of the WCAG (Web Content Accessibility Guidelines) 2.0 standard. The research also identified the common accessibility design issues found in most of Malaysian news websites. The result of this study shows that none of the Malaysian news website conformed with WCAG 2.0 standard. The websites fail to provide an alternative text to convey the information for non-text content in their websites. Therefore, serious improvement is needed to improve the accessibility of the websites with the aim to provide the universal access websites.Â